Building blocks of social cognition: Mirror, mentalize, share?. (September 2019) - Alcalá-López, Daniel; Vogeley, Kai; Binkofski, Ferdinand; Bzdok, Danilo
Abstract: During the past decade, novel approaches to study social interaction have expanded and questioned long-standing knowledge about how humans understand each other. We aim to portray and reconcile the key psychological processes and neural mechanisms underlying navigation of the social environment. Theoretical accounts mostly revolved around either abstract inferences or embodied simulations, whereas experimental studies mostly focused on theory of mind or mentalizing, empathy, and action imitation. The tension between theories of and experiments on social cognition is systematically revisited to foster new theoretical and empirical studies in the fields. We finally retrace differential impairments in social capacities as a means to re-conceptualize psychopathological disturbance in psychiatry, including schizophrenia, borderline personality, and autism.